Inovasi Pembelajaran Pendidikan Agama Islam dengan Menggunakan Media Website di Era Kemajuan Teknologi 4.0 - Ina Maryana; Fuad Hilmi (Gunung Djati Conference Series, 2022)
Technological advances in the 4.0 era have a very significant impact on the world of education, especially in learning Islamic religious education. This requires us as educators to strive to balance these advances so that the learning process is not monotonous by using only one learning method. The website is an alternative as a learning medium that can be used in the current era of technological advancement 4.0, so that the learning process can be done anytime and anywhere. Thus the purpose of this research is to examine more deeply about the innovation of Islamic religious education learning by using the website media in the era of technological advancement 4.0. This type of research is a qualitative research using the library research method as outlined descriptively. In the era of technological advancement 4.0, the relevant Islamic religious education learning media used today is website media. Because the website can provide convenience and speed in conveying information so that the learning process of Islamic religious education can run effectively and efficiently. So that the learning objectives can be achieved properly.